2017
DOI: 10.1073/pnas.1617260114
|View full text |Cite
|
Sign up to set email alerts
|

Flow-assisted assembly of nanostructured protein microfibers

Abstract: Some of the most remarkable materials in nature are made from proteins. The properties of these materials are closely connected to the hierarchical assembly of the protein building blocks. In this perspective, amyloid-like protein nanofibrils (PNFs) have emerged as a promising foundation for the synthesis of novel bio-based materials for a variety of applications. Whereas recent advances have revealed the molecular structure of PNFs, the mechanisms associated with fibril-fibril interactions and their assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
115
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 36 publications
4
115
1
Order By: Relevance
“…As previously reported by others for the brillation of pure b-lactoglobulin 24 and recently also by us for WPI brillation, 25 the morphologies of the brils formed at low and high concentrations differ. At lower concentrations (10-40 g l À1 ), straight brils that are up to a few micrometers long were observed (Fig.…”
Section: -19supporting
confidence: 75%
See 2 more Smart Citations
“…As previously reported by others for the brillation of pure b-lactoglobulin 24 and recently also by us for WPI brillation, 25 the morphologies of the brils formed at low and high concentrations differ. At lower concentrations (10-40 g l À1 ), straight brils that are up to a few micrometers long were observed (Fig.…”
Section: -19supporting
confidence: 75%
“…We recently demonstrated that the same morphological switch is also observed for PNFs from WPI. 25 Interestingly, we also found that the two classes of PNFs display different behavior in the assembly of micrometer-sized laments. The fact that amyloidogenic polypeptides can form brils with different morphologies (strains) and also propagate the structural features through seeding is recognized.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, the BSA fiber is superior to the pseudo‐protein and phage virus fibers in breaking strength . Additionally, the robust mechanical performance in the present BSA system is significantly stronger than that of any other reported globular protein‐based fibers …”
Section: Resultsmentioning
confidence: 78%
“…In order to assemble nanofibrils into microsized fibers, wet‐spinning, dry‐spinning, and microfluidic techniques have previously been explored. In particular, microfluidic spinning has been demonstrated as a powerful technique for the assembly of nanoscale building blocks, such as cellulose fibrils, carbon nanotubes, and graphene fibers in a controlled manner, where the flow of solutions is confined within micrometer scale channels .…”
mentioning
confidence: 99%